2020
DOI: 10.1115/1.4045657
|View full text |Cite
|
Sign up to set email alerts
|

Validation Studies of Linear Oscillating Compressor Cascade and Use of Influence Coefficient Method

Abstract: Advanced predictions of blade flutter have been continually pursued. It is noted however that validation cases of unsteady CFD methods against experimental cases with detailed 3D unsteady pressures are still rather lacking. The main objectives of the present work are two-folds. First, validate and understand the characteristics of blade tip clearance, as well as a bubble-type flow separation for an unsteady CFD solver against a 3D oscillating cascade experiment. And second, examine the applicability of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…High-fidelity models such as LES [57] have been shown to be effective in capturing the formation of laminar separation bubble and the associated transition. In the previous computational study [58], it was shown that using the two-equation - transition correlation coupled with the RANS SST model [59] is also able to predict the formation of separation bubble. Figure 5 compares the experimental steady pressure distribution at mid-span to that predicted by the fine mesh solution with different turbulence models, confirming the previous findings.…”
Section: Validation Of Steady/time-averaged Source Termmentioning
confidence: 99%
“…High-fidelity models such as LES [57] have been shown to be effective in capturing the formation of laminar separation bubble and the associated transition. In the previous computational study [58], it was shown that using the two-equation - transition correlation coupled with the RANS SST model [59] is also able to predict the formation of separation bubble. Figure 5 compares the experimental steady pressure distribution at mid-span to that predicted by the fine mesh solution with different turbulence models, confirming the previous findings.…”
Section: Validation Of Steady/time-averaged Source Termmentioning
confidence: 99%
“…A separation bubble formation around 40 -60% chord can be observed in the experiment. Interestingly, this separation bubble can only be captured in the computation if the transitional turbulence model is used [31]. Instead, a rather smooth pressure distribution at this region is captured with the fully turbulent model.…”
Section: Validationsmentioning
confidence: 99%
“…For more details and analyses for the validation of the tuned oscillating cascade in the bending mode, particularly for the effects of laminar separation bubble and tip clearance, one is referred to Ref. [31].…”
Section: Validationsmentioning
confidence: 99%
“…Inlet endwall boundary layer thickness is another factor of uncertainty [10][11][12]. According to Denton [10], it is perhaps the most important factor and also the least likely to be known.…”
Section: Effects Of Inlet Endwall Boundary Layer Thicknessmentioning
confidence: 99%
“…In addition, a variety of turbomachinery predictions has been shown to be greatly influenced by the inflow boundary conditions [10][11][12][13][14]. From the literature, the turbine vane aero-thermal performance is also affected by the inflow conditioning.…”
Section: Introductionmentioning
confidence: 99%